K problematiki eseja - Štuhec, Miran (Slavistična revija, 2002)
Many well-known Slovene writers, artists, (literary) historians, and critics have concerned themselves with the essay as a special stylistic, linguistic, and psychological "challenge". In the nineteenth century there were only rare examples of the essay, whereas in the twentieth century it placed on the agenda all the most important events in the fields of literature, aesthetics, criticism and the nationality question. This and the growth in the interest in essay writing after 1980 are sufficent reasons to engage in a new reflection on its poetics.
Keywords: esej; esejistika; literarna teorija; literary theory; poetika; Slovene literature; slovenska književnost